A tale of two ceilings: the Capella Palatina in Palermo and the Mouchroutas in Constantinople - Johns, J (Gingko Library, 2017)
I shall argue that Mouchroutas was the name that Mesarites, who alone uses the word, gave for literary purposes to the royal hall built by the emperor Manuel Komnenos in or before the late 1150s. The Manouēlites, as it was known in the 12th and 13th centuries, was a long, rectangular building of two storeys, running north-south. The upper storey consisted of a columned basilica with an apse in the south end to hold an imperial throne. Its walls were decorated with mosaics and it was covered by a wooden, coffered, muqarnas ceiling, resembling that of the Cappella Palatina in Palermo. The carpenters who built both ceilings, and the artists who painted them, came from the Fāṭimid Mediterranean; indeed, I believe that the two ceilings may have been the work of the same workshop. Although the Mouchroutas was no Persian pavilion, the tiles and painted chevrons that decorated the staircase leading up to the hall may very well have come from Saljūq lands. Like the Cappella Palatina, the Mouchroutas deliberately juxtaposed a variety of imported exotic elements in order to demonstrate the range and universality of the ruler’s power. In both royal halls, the dominant aesthetic was cultural diversity, not homogeneity.